Pengaruh promosi, harga dan loyalitas pelanggan terhadap keputusan pembelian produk minyak gemuk di PT. Cipta Sarana Jaya Abadi - Putri Yosevina Purba; Ninta Katharina; Ricky Govindo; Rico Gunawan (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the effect of promotion, price, and customer loyalty on purchasing decisions of fat. The research sample was 75 customers of PT. Cipta Sarana Jaya Abadi was taken by random sampling. The analysis tool uses multiple regression models. The study results found that the purchasing decision of grease was significantly influenced by promotion, price, and customer loyalty. Based on this, the company needs to increase promotions and the best prices for customers and prospective customers and provide satisfactory services to increase customer loyalty to repeat or continuous purchases.